2015
DOI: 10.1097/ccm.0000000000001303
|View full text |Cite
|
Sign up to set email alerts
|

High Level of Endotoxemia Following Out-of-Hospital Cardiac Arrest Is Associated With Severity and Duration of Postcardiac Arrest Shock*

Abstract: In patients successfully resuscitated from cardiac arrest with a postcardiac arrest shock, high level of endotoxemia is independently associated with duration of postcardiac arrest shock and the amount of vasopressive drugs. Whether treatment targeting endotoxemia could be beneficial in the management of postcardiac arrest shock needs to be studied in further randomized controlled studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
29
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(38 citation statements)
references
References 38 publications
5
29
0
2
Order By: Relevance
“…That said, it is important to consider that acute brain injury also induces gut dysbiosis and the associated release of bacterial endotoxin. 39,40 Given studies from our group and others demonstrating the combined effects of damage-associated molecular pattern and pathogen-associated molecular pattern priming postischemic brain injury, 9,41 it will be interesting to test whether fluctuations in systemic arterial SOD3 levels exert similar effects on the enteric microvasculature with attendant effects on associated bacterial translocation and endotoxin leak. The selectivity of the surfactant protein-C promoter and the immunologically distinct human form of SOD3 provided additional insight regarding potential mechanisms leading to neurovascular protection in our model.…”
Section: Discussionmentioning
confidence: 99%
“…That said, it is important to consider that acute brain injury also induces gut dysbiosis and the associated release of bacterial endotoxin. 39,40 Given studies from our group and others demonstrating the combined effects of damage-associated molecular pattern and pathogen-associated molecular pattern priming postischemic brain injury, 9,41 it will be interesting to test whether fluctuations in systemic arterial SOD3 levels exert similar effects on the enteric microvasculature with attendant effects on associated bacterial translocation and endotoxin leak. The selectivity of the surfactant protein-C promoter and the immunologically distinct human form of SOD3 provided additional insight regarding potential mechanisms leading to neurovascular protection in our model.…”
Section: Discussionmentioning
confidence: 99%
“…The use of low-dose endotoxin as a driver of PCAS pathology is a unique feature of this work and is based on reports from the clinical literature citing the association between serum endotoxin and the duration of post cardiac arrest shock (Grimaldi, et al 2013, Grimaldi, et al 2015). Mesenteric ischemia stimulates the growth of gram-negative bacteria in situ and induces villous blunting with mucosal degeneration (Karhausen, et al 2013, L’Her, et al 2005, Wang, et al 2012).…”
Section: Discussionmentioning
confidence: 99%
“…In our initial dose ranging studies, we found the delivery of LPS above 1 mg/kg after the 3VO procedure caused a high rate of perioperative mortality (data not shown). We, therefore, adjusted our dosing strategy reducing the amount of LPS (50 μg/kg) to a point where serum endotoxin was undetectable, such as has been described for a significant number of patients (Grimaldi, et al 2015). Although low-dose endotoxin challenge was not detected in serum using the limulus amebocyte lysate assay, which is sensitive to levels as low as 0.1 EU/ml (or approximately 0.01 ng endotoxin/ml), its use in our paradigm resulted in the activation of brain endothelium, damage to the BBB with the accumulation of serum proteins in the parenchyma, microglial activation, and the accumulation of PMNs in areas of cortical ischemia.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations